(untitled) (Journal on studies and research of academic knowledge, 2016)
The intention of this work is a participatory research and diagnosis of two indigenous communities of the Department of Itapúa, the Maka of Ita Paso (District of Trinidad) and the Mbya Guaraní of Guavirami (District of Trinidad). Taking the communities, their leaders and their members’ own views and actions as the main perspective, the research illustrates the interdependent economic, social and cultural components of their well-being or "good living". This makes visible such components and contribute to the communal actions that perform them.